MADRASAH-BASED MANAGEMENT IN IMPROVING QUALITY EDUCATION - Alwi, Toto; Annur, Saipul; Firdaus, Ramdhan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The organization is where people gather and work together rationally and systematically in utilizing organizational resources efficiently and effectively to achieve predetermined goals. This directed collaboration is carried out by following the interaction pattern between each individual or group in and outside the organization. The interaction pattern is aligned with various rules, norms, beliefs, and specific values as determined by the organization; the interaction pattern within a specific time will form a familiar habit or an organizational culture that always controls the organization's members. Thus a solid organizational culture is a form of organizational performance. Tall one. In management, organizing/organizing is something that is needed. Why is that because of organization, including a form of realization/execution of the initial management plan? Therefore organizing is a means to achieve organizational goals by utilizing the maximum available tools. Keywords: Madrasah-Based Management, Quality of Education, Management Education